A new miniature species of the milliped genus Cleidogona from Costa Rica (Diplopoda, Chordeumatida, Cleidogonidae), with a review of Central American Cleidogonidae - Shear, William A. (Zootaxa, 2013)
Cleidogona huebnerae, n. sp., is described from La Gamba Tropical Research Station,Costa Rica. A total of sixteen species in three genera of Cleidogonidae are known fromCentral America (Guatemala south toPanama), and they are reviewed here.